A Scope Analysis on Tax Amnesty Toward Taxpayer Compliance in Paying Taxes in Samarinda-Indonesia - La Ode Hasiara; Sailawati Sailawati (Pusat P2M Politeknik Negeri Batam, 2022)
The study aims to examine and test the quality of service of the tax authorities, tax payer education related to taxpayer compliance, application of tax sanctions, socialtizations on taxpayer compliance, and taxpayers’ knowledge on on compliance in Samarinda, East Kalimantan. This study uses a quantitative descriptive approach, by using SPSS Version 20. The results of this study indicate that the quality of tax authorities, taxpayer education, tax sanctions, socialization to taxpayers and knowledge of influential taxpayers have a significant impact on taxpayer compliance in Samarinda, East Kalimantan. The R2 is 0,292 or 29%, meaning that the variables affect compliance by 29% and the remaining 71% is influenced by other variables outside of this study. Simultaneously and partially, the quality of tax authorities, education of taxpayers, application of tax sanctions, socializations to taxpayers, and initial taxpayers’ knowledge on compliance have a significant effect on compliance.